Design and Implementation of an IoT-Based Smart Drip Irrigation System Using Takagi-Sugeno Fuzzy Logic for Melon Cultivation - Dian Pertiwi, Kharisma Monika; Nur Alif, Muhammad Sufi (Journal of Applied Informatics and Computing, 2025)
The melon plant (Cucumis melo L.), a species of the Cucurbitaceae family, requires precise water management to support optimal growth. This study developed an Internet of Things (IoT)-based innovative irrigation system employing Takagi-Sugeno fuzzy logic to regulate water supply for melon cultivation in a greenhouse. The system integrates a capacitive soil moisture sensor and a DS18B20 temperature sensor, both connected to an ESP8266 microcontroller, which controls a solenoid valve used in the drip irrigation method. Sensor data are transmitted in real-time to Firebase Realtime Database (cloud platform) for monitoring through a web-based interface. The solenoid valve opening duration ranges from 0 to 720 seconds per irrigation session, dynamically adjusted according to soil moisture and temperature inputs. Experimental results demonstrate that the proposed system effectively maintains soil moisture within the optimal range of 60%–80%. However, plant growth evaluation indicates that the system has not fully promoted healthy development, particularly in plant height and leaf width, likely due to additional factors such as soil conditions, humidity, and nutrient availability. Despite these limitations, the proposed smart irrigation system shows strong potential for further refinement to enhance water efficiency and support sustainable melon cultivation.